Reduced Serotonin-1A Receptor Binding in Social Anxiety Disorder - Lanzenberger, Rupert R.; Mitterhauser, Markus; Spindelegger, Christoph; Wadsak, Wolfgang; Klein, Nikolas; Mien, Leonhard-Key; Holik, Alexander; Attarbaschi, Trawat; Mossaheb, Nilufar; Sacher, Julia; Geiss-Granadia, Thomas; Kletter, Kurt; et al. (Biological psychiatry (1969), 2007)
Results from studies in serotonin-1A (5-HT 1A) knockout mice and previous positron emission tomography (PET) studies in humans imply a role for 5-HT 1A receptors in normal state anxiety as well as in certain anxiety disorders. The objective of this study was to investigate 5-HT 1A receptor binding potential (BP) in social anxiety disorder (SAD). Using PET and [carbonyl- 11C]WAY-100635, we compared a homogeneous group of 12 unmedicated, male SAD patients with 18 healthy control subjects (HC). A multivariate ANOVA with all regional BP values as dependent variables, age and four radiochemical variables as covariates was performed. We found a significantly lower 5-HT 1A BP in several limbic and paralimbic areas but not in the hippocampus (p = .234) of SAD patients. The difference in 5-HT 1A binding was most significant in the amygdala (−21.4%; p = .003). There was also a more than 20% lower 5-HT 1A BP of SAD patients in the anterior cingulate cortex (p = .004), insula (p = .003), and dorsal raphe nuclei (p = .030). The lower 5-HT 1A binding in the amygdala and mesiofrontal areas of SAD patients is consistent with 1) preclinical findings of elevated anxiety in 5-HT 1A knockout mice, 2) a previous PET study in healthy volunteers showing an inverse correlation between 5-HT 1A BP and state anxiety, and 3) another human PET study in patients with panic disorder showing reduced 5-HT 1A binding, thus corroborating the potential validity of 5-HT 1A receptors as targets in the treatment of human anxiety disorders.